Molecular cloning of unintegrated Moloney mouse sarcoma virus DNA in bacteriophage lambda. - Verma, I M (1980)
The covalently closed circular forms of unintegrated viral DNA obtained from cells infected with Moloney mouse sarcoma virus was cloned in bacteriophage lambda. The viral DNA was cleaved with restriction endonuclease HindIII and inserted in the unique HindIII site of lambda Charon 21A DNA. Recombinant clones containing virus-reactive DNA sequences were analyzed by restriction endonuclease mapping, R-loop formation, and infectivity assays. Two of eight genome-length recombinant clones characterized contained the large terminal repeat. Only the recombinant clones containing the large terminal repeat were able to induce focus formation in uninfected mouse fibroblasts.